A Systematic Literature Review of Digital Payment in Ethiopia: Challenges, User Satisfaction, and Socio-Economic Impact - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
This systematic literature review examines the challenges, user satisfaction determinants, and socio-economic impact of digital payments in Ethiopia. Following PRISMA guidelines, a comprehensive search of Scopus, Web of Science, Google Scholar, the Addis Ababa University Institutional Repository, and African Journals Online was conducted, covering literature published between 2015 and 2026. The review synthesises findings from peer-reviewed journal articles, institutional reports, and postgraduate theses, employing the Technology Acceptance Model and Diffusion of Innovation theory as analytical frameworks. The findings reveal that while Ethiopia's digital payment ecosystem has experienced remarkable growth, exemplified by Telebirr's 46.6 million users and digital transactions exceeding 18 trillion Birr annually, persistent challenges impede the transition from access to meaningful usage. Five interconnected categories of barriers are identified: infrastructure deficits, trust and security concerns, economic and affordability barriers, organizational and institutional weaknesses, and socio-cultural factors. Trust emerges as the critical mediating factor between service provision and user satisfaction, serving as the primary adoption driver. User satisfaction is determined by trust, convenience, speed, security, cost, and user experience, with integrated theoretical models demonstrating strong predictive power (R² = 0.675). Socio-economic benefits are evident across financial inclusion, economic formalization, social empowerment, and enterprise development, though benefits remain unevenly distributed. The National Bank of Ethiopia's Digital Payment Strategy 2026–2030 represents a necessary policy reorientation toward trust-building and active usage. Recommendations include strengthening digital infrastructure, reducing transaction costs, enhancing consumer protection, and prioritizing gender-responsive innovation.